Rana arvalis Nilsson, Viviparous Lizard 1842 ... - Elmberg, Johan (Studia Slavica et Balcanica Petropolitana, 2023)
Moor Frog Rana arvalis Nilsson 1842 Distribution (Figure 6). Included records from Artportalen (N=650): as confusion with Rana temporaria is possible, reports from the Alpine region, the Northern Boreal region and all offshore sites were included only if substantiated by photos, concern calling males, or made by known experienced observers. Reports from the Southern and Middle Boreal were all included. Widespread and common in the Southern and Middle Boreal. For unknown reasons more abundant in landscapes with flatter topography (Sterner 2005; Elmberg 2008), a pattern also noted in Finland (Terhivuo 1981). Widespread but less common in the Northern Boreal, scarce in its higher parts. The northernmost Swedish record is at Kulijärvi, Torne lappmark (67° 50’ N, 21° 40’ E; Elmberg 1984). Previous records from the Alpine region (e.g., Elmberg 1995) are now considered as unconfirmed and not valid. The highest known records are very close to the border between the Northern Boreal and the Alpine regions: 580–600 m ... : Published as part of Elmberg, Johan, 2023, Amphibians and reptiles in North Sweden: distribution, habitat affinities, and abundance (Classes: Amphibia and Reptilia), pp. 301-335 in Zootaxa 5301 (3) on pages 315-316, DOI: 10.11646/zootaxa.5301.3.1, http://zenodo.org/record/8030434 ...